UJI FISIK DAN UJI IRITASI SEDIAAN MASKER GEL EKSTRAK ETANOL DAUN DEWA (Gynura pseudochina (Lour.) DC.) - Ummi Nurus Salamah; Muhammad Nurul Fadel; Eko Retnowati (Nusantara Hasana Journal, 2025)
The gel mask preparation containing (Gynura pseudochina) extract was evaluated through physical and irritation tests, including organoleptic observation, homogeneity, pH, viscosity, spreadability, adhesion, drying time, and potential skin irritation. Organoleptic results showed that all formulas had consistent color, odor, and texture, aligning with topical product standards. Homogeneity testing confirmed that the formulations were evenly mixed without visible clumps or phase separation. The pH values ranged between 5 and 6, which are considered safe and comfortable for skin application. The addition of extract affected viscosity levels low to moderate concentrations increased thickness, while higher concentrations led to a decrease due to disruption of the gel matrix structure. Spreadability and adhesion tests indicated that all formulas had appropriate consistency for topical use, allowing ease of application and suitable adherence to the skin. Drying times were consistent across formulas, supporting efficient user experience. Irritation testing revealed no visible reactions on the skin, indicating that all formulas are safe for topical application.